Students’ and Teachers’ Perception, and Parents’ Role in the Implementation of High School Physical, Sports, and Health Education Subject in East Kutai - Rizki SP, Tri Agustin Wulandari; Setyawati, Heny; Rumini, Rumini (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
This study aimed at analyzing the perceptions of students, teachers and parents on the implementation of Physical, Sports, and Health Education (called PJOK) subject, analyzing the role of students, teachers and parents on the construction of PJOK learning planning, analyzing students, teachers and parents understanding and position on the construction of PJOK learning planning. This research was a kind of quantitative descriptive research. The population in this study was 8 Public Senior High School in East Kutai, while the sample was 10% of the total number of student respondents from 8 state high schools drawn by the proportional stratified random sampling technique consisted of 754 respondents. The data were collected through surveys and interviews. The results revealed that students’ and teachers’ perceptions, and parents’ role in the implementation of PJOK subject was good, students’ and teachers’ understanding, and parents’ role in the implementation of PJOK subject was sufficient, students’, teachers’ and parents’ role in the implementation of PJOK subject was sufficient. This research also provided some suggestions including PJOK teachers and parents should pay attention to students as subjects in education who have roles and positions that must be considered in learning, the government needs to provide clear guidelines and be concerned with the implementation of education through a curriculum system that is under the subject principles in education in which the subject is the student.